Analisis Implementasi Keamanan Data Berbasis Teknologi Blockchain pada Sistem Manajemen Informasi - Muhammad Khairul Imam (Jurnal Riset Multidisiplin Edukasi, 2026)
The development of blockchain technology has brought significant changes in data security and transparency within information management systems. This research aims to design and test the effectiveness of a private blockchain system based on the Hyperledger Fabric framework as a secure and decentralized data storage solution. The methodology employed is an experimental approach by constructing block structures consisting of index, timestamp, hash, and previous hash. System testing focused on three main parameters: throughput (TPS), latency, and data integrity through varied workload scenarios. Research findings demonstrate that the system maintains stable performance under moderate workloads with throughput of 370-450 TPS and latency below 210 milliseconds. Integrity testing proves that every illegal data modification attempt is automatically rejected by the cryptographic hashing mechanism with 100% detection accuracy. In conclusion, this private blockchain architecture provides superior security levels by reducing data manipulation risks up to 99.8% for professional data recording needs requiring strict access control without compromising operational system performance.